Ultra-stable Eu3+/Dy3+co-doped CsPbBr3 quantum dot glass nanocomposites with tunable luminescence properties for phosphor-free WLED applications - Erol, Erdinc; Vahedigharehchopogh, Naji; Ekim, Utku; Uza, Nazlican; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin (ELSEVIER SCIENCE SA, 2022)
Colloidal CsPbBr3 perovskite quantum dots (PQDs) have substantially improved modern optoelectronic applications, including solid-state lighting, thanks to their highly pure and intense green light emission. However, some drawbacks including lead toxicity, poor stability, and difficulties in emission color tuning hinder their practical applications. Herein, ultra-stable Eu3+/Dy3+ co-doped CsPbBr(3 )PQD glass nano-composites (GNCs) with tunable color emissions from green to red and then white are synthesized via melt-quenching followed by heat-treatment method to be used in white light-emitting diodes (WLEDs). Eu3+ and Dy3+ ions are selected to overcome the color tunability obstacle of PQDs and to obtain phosphor-free white light emission with enhanced CRI values. The photoluminescent performance of GNCs is shown to be reversible at elevated temperatures and remains stable even in water. Ultimately, a prototype WLED is constructed by coupling a selected Eu3+/Dy3+ co-doped CsPbBr3 PQD GNC on top of a 400 nm-emitting LED chip to demonstrate its superior optical performance with a color rendering index of 78 and correlated color temperature of 5436 K. The developed GNCs with long-term stability, and excellent tunable luminescent properties may overcome the commercialization barriers of CsPbBr3 PQDs for WLED applications. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: CsPbBr 3; Quantum dots; Lanthanides; Tunable emission; Solid-state lighting; WLED; LIGHT-EMITTING-DIODES; PHOTOLUMINESCENCE PROPERTIES; OPTICAL-PROPERTIES; RED PHOSPHORS; PEROVSKITE; NANOCRYSTALS; COMPOSITE; LANTHANIDE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering